Accuracy in UAS GPS Coordinates in Response To Speed - Chebultz, Stefan; McCornack, Brian; Bhattarai, Ganesh; Mills, Colton (My University, 2018)
The purpose of this experiment was to find how much of a difference in GPS accuracy on a UAS system in relation to speed there was (if any) in comparison to an absolute (1-2 cm accuracy) known location provided by a ground station. We began by placing identification makers in a straight line, setting up a TopCon ground station and positioning each of them to an absolute GPS coordinate, and flying a Mavic Pro UAS with GPS positioning abilities over each of the identification markers. After many runs at different hover times, speed and altitude, we found that the GPS coordinates from the UAS would not match with the absolute location of the TopCon.
Keywords: Fall 2018